2024
DOI: 10.1037/tra0001248
|View full text |Cite
|
Sign up to set email alerts
|

Pathways to resilience: The parallel change in children’s emotional difficulties and family context during the COVID-19 lockdown in Italy.

Abstract: Objective:The study analyses which pathways to adjustment emerged at the family level during the COVID-19 containment period in Italy, during which children were locked down with their families for 56 days from March 11 to May 6. Using a longitudinal design, with data pre-and postevent, a bivariate latent change score model analyzed the covariance of the change in family well-being (FW) and in emotional difficulties (ED), testing if the longitudinal change in ED is a function of the starting level of FW, and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Changes to children’s family conditions during the pandemic may influence how they respond to stress during the pandemic. Although baseline family well-being did not significantly predict later internalizing problems in children, increases in family well-being from prepandemic to during COVID-19 were associated with decreases in child internalizing problems (Nocentini et al, 2022). Furthermore, increases in family conflict and decreases in the quality of emotional connections among family members (i.e., family cohesion) were predictive of heightened child internalizing problems during the pandemic, while baseline levels were not (Fosco et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Changes to children’s family conditions during the pandemic may influence how they respond to stress during the pandemic. Although baseline family well-being did not significantly predict later internalizing problems in children, increases in family well-being from prepandemic to during COVID-19 were associated with decreases in child internalizing problems (Nocentini et al, 2022). Furthermore, increases in family conflict and decreases in the quality of emotional connections among family members (i.e., family cohesion) were predictive of heightened child internalizing problems during the pandemic, while baseline levels were not (Fosco et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Across several pathways, Fosco et al (2022) found more support for change in family dynamics (e.g., conflict, cohesion, and discipline) predicting child maladjustment rather than initial scores of the same measures. Similarly, another study demonstrated that baseline family well-being did not predict change in child emotional difficulties; rather, change in family well-being covaried with change in child emotional difficulties (Nocentini et al, 2022). Essler et al (2021) also provided support for change scores in parental strain predicting intraindividual change in child emotional well-being.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations